The study and research of self-presentation’s motivation in its manifestation in the transition period from primary school to adolescence - Kapustiuk Olena; Pastushenko Valentyna (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2016)
The article summarizes the results of national and international research self-presentation phenomenon and motivation of its manifestation in the transitional period from primary school to adolescence. Was allocated two groups of indicators functioning of the presentation of the phenome- non during childhood: cognitive and behavioral. It is confirmed the formation of understanding and perception of young schoolchildren’s tactics of the self-presentation: the intensive development of the system of cognitive representations, the actualization of the self-presentation motivation, its implementation at the behavioral level. Picked up the complex of methods which to track particular qualities of the self-presentation in the condi- tions of activity self-realization in the educational space.